CHARACTERISTICS OF RENAL CANCER PATIENTS IN HAJI ADAM MALIK GENERAL HOSPITAL MEDAN IN THE YEAR 2011 -2015 - Kurnia, Riyan Adi; Kadar, Dhirajaya Dharma; Prapiska, Fauriski Febrian (Indonesian Journal of Urology, 2018)
Objective: The aim of this study is to identity the characteristics of kidney cancer patients at Haji Adam Malik Hospital between 2011 and 2015. Material & methods: This is a retrospective descriptive study of all kidney cancer patients treated at Haji Adam Malik Hospital between 2011 and 2015. Individual patient data was collected from medical record and compiled. Results: Between 2011 and 2015, there were 38 patients diagnosed with kidney cancer treated at Haji Adam Malik Hospital. The patients mean age is 48.26 ± 14.68 years, with a male to female ratio 1.7:1. Histological type found in the study was RCC (57.15%), urothelium based (19.05%), sarcoma variant (14.28%) and benign kidney tumor (9.52%). Clear cell RCC (58.3%) is the most common type of RCC. Based on the TNM classification, patients with kidney tumor of stage II, stage III and stage IV are 15.8%, 10.5% and 73.7% respectively. The treatment modalities for kidney cancer are nephrectomy (44.7%), nephroureterectomy (2.6%), biopsy (8.0%) and inoperable patients or treatment refusal (44.7%). The mortality rate of kidney cancer patients was 81.5%. Conclusion: Mean age of kidney cancer patients at Haji Adam Malik Hospital was lower than that reported in literature. Gender ratio was found similar as seen in literature. The ratio of histological type was differ, but we still found RCC as the most common type of kidney malignancies. Higher number of patients presented at advance stage at diagnosis and refusal to treatment may contribute to the high mortality rate in this study.